Seven new taxa of Leptodirini (Coleoptera: Leiodidae: Cholevinae) from the Balkan Peninsula - Ćurčić, Srećko; Pavićević, Dragan; Vesović, Nikola; Mulaomerović, Jasminko; Rađa, Tonći; Antić, Dragan; Bosco, Fabrizio; Marković, Đorđe; Petković, Matija (Zootaxa, 2018)
Seven new troglobitic leiodid beetle taxa (six new species and one new subspecies) from several caves and pits in the Balkan Peninsula (Bosnia and Herzegovina and Serbia) are described and diagnosed. Three new species belong to the genus Adelopidius Apfelbeck, 1907, two—to the genus Pholeuonopsis Apfelbeck, 1901, one—to the genus Leonhardia Reitter, 1901, while a new subspecies belongs to the genus Apholeuonus Reitter, 1889. All important morphological characteristics of the new taxa have been mentioned and imaged, including the aspects of the male and female genitalia. The new leiodid taxa are properly distinguished from their relatives and are endemics of the Dinaric mountain chain. A key to Adelopidius taxa is added.